The Relationship between Emotional Labor and Emotional Exhaustion “A Field Study on Nurses in Private Hospital in Amman” - Al Ma’aitah, Arwa; Alsawalqa, Rula (Dirasat: Human and Social Sciences, 2021)
This study aims to explore the relationship between the emotional labor of nurses and emotional exhaustion. Also, aims to examine the relationship between the emotional labor of nurses and each of the variables: Age, work department, the social status, shift, Job satisfaction, and the nurse’s job position. The Emotional labor Scale and Emotional Exhaustion Scale were used as a data collection tool. The study population consisted of all (42) private hospitals in the capital, Amman. A regular random sample of (494) nurses was chosen from five private hospitals in the capital, Amman. The results revealed that Levels of emotional labor and emotional exhaustion were moderate for nurses. Moreover, there is a positive correlation between the emotional labor and the emotional exhaustion among nurses. However, in practicing emotional labor, nurses rely more on deep acting than superficial acting. And the dimensions of the emotional labor of the nurses came in the following order (duration, frequency, diversity, deep acting, superficial acting) Also, there were statistically significant differences in the levels of emotional labor among nurses due to the variables of (age, work department and Job satisfaction). In light of these results, the study recommended that hospital officials should provide emotional support to nurses in order for them to increase their ability to summon the appropriate emotional response during interaction with patients, and to protect them from the negative effects of emotional labor.